Using Seabird Habitat Modeling to Inform Marine Spatial Planning in Central California’s National Marine Sanctuaries - McGowan, Jennifer (Public Library of Science, 2013)
Understanding seabird habitat preferences is critical to future wildlife conservation and threat mitigation in California. The objective of this study was to investigate drivers of seabird habitat selection within the Gulf of the Farallones and Cordell Bank National Marine Sanctuaries to identify areas for targeted conservation planning. We used seabird abundance data collected by the Applied California Current Ecosystem Studies Program (ACCESS) from 2004–2011. We used zero-inflated negative binomial regression to model species abundance and distribution as a function of near surface ocean water properties, distances to geographic features and oceanographic climate indices to identify patterns in foraging habitat selection. We evaluated seasonal, inter-annual and species-specific variability of at-sea distributions for the five most abundant seabirds nesting on the Farallon Islands: western gull (Larus occidentalis), common murre (Uria aalge), Cassin’s auklet (Ptychorampus aleuticus), rhinoceros auklet (Cerorhinca monocerata) and Brandt’s cormorant (Phalacrocorax penicillatus). The waters in the vicinity of Cordell Bank and the continental shelf east of the Farallon Islands emerged as persistent and highly selected foraging areas across all species. Further, we conducted a spatial prioritization exercise to optimize seabird conservation areas with and without considering impacts of current human activities. We explored three conservation scenarios where 10, 30 and 50 percent of highly selected, species-specific foraging areas would be conserved. We compared and contrasted results in relation to existing marine protected areas (MPAs) and the future alternative energy footprint identified by the California Ocean Uses Atlas. Our results show that the majority of highly selected seabird habitat lies outside of state MPAs where threats from shipping, oil spills, and offshore energy development remain. This analysis accentuates the need for innovative marine spatial planning efforts and provides a foundation on which to build more comprehensive zoning and management in California’s National Marine Sanctuaries.